Effects of Straw Mulching Thickness on the Soil Health in a Temperate Organic Vineyard - Tianyu Qin; Lan Wang; Jianshe Zhao; Gaifang Zhou; Caihong Li; Liyue Guo; Gaoming Jiang (Agriculture, 2022)
Soil mulching is one of the common measures applied in organic agricultural production which could replace plastic films and protect the environment. In order to fully evaluate the effects of different straw mulching thicknesses on soil health, maize straw was mulched with the thicknesses of 0 cm (CK), 2 cm, 4 cm and 6 cm on soil surface to assess the effects on soil temperature (ST) and moisture (SM), soil pH, soil organic carbon (SOC), total nitrogen (TN), C/N, soil aggregates and soil bulk density (SBD) in a temperate organic vineyard. We found that straw mulching had a significant regulating effect, with soil moisture being elevated with increasing mulching thickness by 5.8%, 9.0% and 11.1% compared with CK. The soil SOC content increased by 3.0%, 2.4% and 2.3%. Although soil pH and C/N significantly (p < 0.05) increased, they fluctuated with increasing mulch thickness. Straw mulching also increased the content of >2 mm soil particle size and elevated the mean weight diameter (MWD) and geometric mean diameter (GMD). The increasing mulching thickness prolonged the effect on the stability of soil aggregates. The 4 cm maize straw mulching thickness has the best effect for ecologically and environmentally managing warm-temperate organic vineyards so it may have a great application prospect on a global scale.